The University of the Philippines Library as reflected in three publications-the Philippine Collegian, the U.P. Newsletter and the Carillon a content analysis - Reyes, Teresita J. (Institute of Library Science, University of the Philippines Diliman, 1980)
This study sought to determine how the policies, services and actions of the University of the Philippines Library (U.P. Library) were reported in three U.P. major publications - the Philippine Collegian, the U.P. Newsletter, and the Carillon from 1970-1975.